2018
DOI: 10.1002/ijc.31296
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the multidrug transporter Patched potentiates chemotherapy efficiency on adrenocortical carcinoma in vitro and in vivo

Abstract: One of the crucial challenges in the clinical management of cancer is the resistance to chemotherapeutics. We recently demonstrated that the Hedgehog receptor Patched, which is overexpressed in many recurrent and metastatic cancers, is a multidrug transporter for chemotherapeutic agents such as doxorubicin. The present work provides evidences that Patched is expressed in adrenocortical carcinoma (ACC) patients, and is a major player of the doxorubicin efflux and the doxorubicin resistance in the human ACC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 43 publications
(52 reference statements)
6
47
0
Order By: Relevance
“…We previously showed that Ptch1 drug efflux inhibition enhanced the cytotoxicity of dxr against adrenocortical carcinoma cells, but also that of cisplatin, another well known chemotherapeutic drug [19], suggesting that both cisplatin and dxr are substrates of Ptch1 [16]. Therefore, we tested the effect of sPAH on the cytotoxicity of cisplatin in the melanoma cell lines MeWo and A375.…”
Section: Spah Enhances the Sensitivity Of Melanoma Cells To Cisplatinmentioning
confidence: 99%
“…We previously showed that Ptch1 drug efflux inhibition enhanced the cytotoxicity of dxr against adrenocortical carcinoma cells, but also that of cisplatin, another well known chemotherapeutic drug [19], suggesting that both cisplatin and dxr are substrates of Ptch1 [16]. Therefore, we tested the effect of sPAH on the cytotoxicity of cisplatin in the melanoma cell lines MeWo and A375.…”
Section: Spah Enhances the Sensitivity Of Melanoma Cells To Cisplatinmentioning
confidence: 99%
“…According to a review article from Papadopoulos and co-workers [ 43 ], Ptch1 is also upregulated in colorectal cancers. Further, immunohistochemical (IHC) analysis on adrenocortical carcinoma (ACC) samples from 70 patients showed that Ptch1 was expressed in ACC tumor tissues from all 70 patients [ 44 ]. Finally, Ptch1 has been proposed to be an early marker for gastric and thyroid cancers [ 45 , 46 ].…”
Section: The Hh Receptor Ptch1 Is Overexpressed In Many Aggressivementioning
confidence: 99%
“…The hypothesis that Ptch1 could be a multidrug transporter involved in chemotherapy resistance has been strongly strengthened by the observation, using Ptch1-silencing RNA, that doxorubicin efflux from the human cell line H295R, which was isolated from a patient diagnosed with an adrenocortical carcinoma (ACC), mainly occurs through Ptch1 and not through ABC transporters such as P-gp [ 44 ]. Notably, doxorubicin is one of the three chemotherapeutic agents that is included in the gold standard ACC therapy which often fails due to resistance to the treatment, leading to poor overall patient survival [ 74 , 75 ].…”
Section: Ptch1 Is a Multidrug Transporter Involved In Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Among several mechanisms that may lead to the development of MDR, the overexpression of ATP-binding cassette (ABC) transporters such as ABCB1 (P-glycoprotein, MDR1: multidrug resistance protein 1), ABCC1 (MRP1: multidrug resistance-associated protein 1), and ABCG2 (BCRP: breast cancer resistance protein) proteins seems to prevail [3,4]. It was recently reported that non-ABC transporters such as Hedgehog receptor Patched were also engaged in doxorubicin (Dox) efflux and conferred Dox resistance to cancer cells [5,6]. ABCB1 is a transporter that utilizes the energy gained from the hydrolysis of ATP to pump many structurally variable substrates (including xenobiotics and chemotherapeutics) out of the cell [7].…”
Section: Introductionmentioning
confidence: 99%